2007
DOI: 10.1152/japplphysiol.00264.2006
|View full text |Cite
|
Sign up to set email alerts
|

Early onset airway obstruction in response to organic dust in the horse

Abstract: Deaton CM, Deaton L, Jose-Cunilleras E, Vincent TL, Baird AW, Dacre K, Marlin DJ. Early onset airway obstruction in response to organic dust in the horse. J Appl Physiol 102: [1071][1072][1073][1074][1075][1076][1077] 2007. First published December 7, 2006; doi:10.1152/japplphysiol.00264.2006.-Equine recurrent airway obstruction (RAO) has been used as a naturally occurring model of human asthma. However, it is unknown whether there is an early-phase response in RAO. The aim of this study was to determine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
2
10
0
1
Order By: Relevance
“…In conclusion, our studies demonstrated that S-salbutamol elicited a weak contraction of equine airway smooth muscle, but induced a significant hyperresponsiveness to histamine that could be detrimental particularly in RAO-affected horses [27][28][29][30]. Our results suggest that it may be prudent to administrate the R-isomer alone in RAO horses to avoid detrimental effect of S-isomer.…”
Section: Discussionmentioning
confidence: 55%
“…In conclusion, our studies demonstrated that S-salbutamol elicited a weak contraction of equine airway smooth muscle, but induced a significant hyperresponsiveness to histamine that could be detrimental particularly in RAO-affected horses [27][28][29][30]. Our results suggest that it may be prudent to administrate the R-isomer alone in RAO horses to avoid detrimental effect of S-isomer.…”
Section: Discussionmentioning
confidence: 55%
“…An immediate allergic response is not typically associated with heaves exacerbation and an early phase (10–20 min) histamine release and bronchoconstriction response to inhaled dust does not occur in diseased horses 46 . A significant histamine release and bronchoconstriction is however reported in healthy controls, suggesting that the early phase response may contribute to reduce the amounts of antigens reaching the peripheral airways and therefore be protective 46 .…”
Section: Aetiology and Pathophysiologymentioning
confidence: 99%
“…An immediate allergic response is not typically associated with heaves exacerbation and an early phase (10–20 min) histamine release and bronchoconstriction response to inhaled dust does not occur in diseased horses 46 . A significant histamine release and bronchoconstriction is however reported in healthy controls, suggesting that the early phase response may contribute to reduce the amounts of antigens reaching the peripheral airways and therefore be protective 46 . Nevertheless, pulmonary mast cells from heaves‐affected horses have a greater in vitro histamine release in response to mould extracts ( A. fumigatus , M. feani , A. tenius ) 47 and greater histamine concentrations are detected in pulmonary epithelial lining fluid from these horses compared with controls 5 h, but not 30 min, after natural antigenic challenge 48 .…”
Section: Aetiology and Pathophysiologymentioning
confidence: 99%
“…Only in healthy horses an immediate allergic reaction can be seen (Deaton et al 2007). This suggests that the reaction of a healthy horse to an inhaled allergen is a protective mechanism which avoids the distribution of the allergen in small airways.…”
Section: Discussionmentioning
confidence: 99%